Effective land ownership, female empowerment, and food security: Evidence from Peru - Maja Schling; Nicolás Pazos (Inter-American Development Bank (IDB), 2021)
This paper examines the effect of women's effective land ownership on female empowerment and household food security in the context of Peruvian family farming. Using an instrumental variable approach, we explore whether self-declared informal ownership of plots provides women with increased bargaining power, empowering them to participate more actively in productive decision-making that leads to improved crop diversity and food security. While our results do not find significant effects of informal land ownership on women's empowerment, we do find that owning land significantly decreases the daily time dedicated to agricultural work, possibly freeing up time for the woman to engage in other activities. Results also show that female land ownership significantly increases the level of crop diversity and improves the households probability of being food secure by 20 percentage points. This suggests that equal access to land, even without formal title, plays an important role in improving household welfare among smallholder family farmers.
Keywords: C26; J1; O12; O13; Q15; Q18; 330; Gender empowerment; food security; land property rights; Peru; Latin America